(untitled) (Research, Society and Development, 2022)
State-controlled territories are subject to aprioristic striations through general norms so that they may be ordered and thus eventually more easily interdicted. On the other hand, such spaces may be smoothed, making them available for unforeseen appropriations. This is the duality of domination and spontaneity, between the capturing apparatuses and the war machines, Gilles Deleuze and Felix Guatarri’s heteronymous pairs. Concomitantly to a hostile urban logic, that places the unwanted guest in the spotlight and marks territories with authority, oppression, rules and segregation — through little territorial actions of inhibition and coercion by means of laws, acts and hostile architectures —, there are also places of hospitality, open receptacles and welcoming places that always make room for the other, any other — such as Khôra, according to Jacques Derrida —, and that points out the right to life and the confrontment to these striations. Using these concepts, it is possible to see the territorializations built from the antinomy between the imposition of control through power and fear and the chance to be welcoming and thus promote unfathomable sharing processes.